2020
DOI: 10.1371/journal.pone.0236540
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the power of eDNA metabarcoding for the detection of deep-sea fishes

Abstract: The deep ocean is the largest biome on Earth and faces increasing anthropogenic pressures from climate change and commercial fisheries. Our ability to sustainably manage this expansive habitat is impeded by our poor understanding of its inhabitants and by the difficulties in surveying and monitoring these areas. Environmental DNA (eDNA) metabarcoding has great potential to improve our understanding of this region and to facilitate monitoring across a broad range of taxa. Here, we evaluate two eDNA sampling pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 57 publications
3
44
1
Order By: Relevance
“…Fish eDNA stratification in the ocean responds to fish vertical distribution Despite the complexity of the vertical structuring of pelagic communities (Sutton 2013) and the call for studies focusing on the deep-sea ecosystem (Mengerink et al 2014;St. John et al 2016;Martin et al 2020), to date just a few studies have used eDNA sampling to explore the deep sea (Thomsen et al 2016;Easson et al 2020;Laroche et al 2020;McClenaghan et al 2020;Govindarajan et al 2021), and none has provided insights on the deep, vertical stratification of eDNA in the ocean. Here, we observed a consistent detection of DNA of the most abundant epipelagic fish species along the water column (e.g., European anchovy is detected down to > 1000 m depth), whereas detection of DNA from deep-sea fish was restricted to the upper depth at which they were assumed to occur and below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish eDNA stratification in the ocean responds to fish vertical distribution Despite the complexity of the vertical structuring of pelagic communities (Sutton 2013) and the call for studies focusing on the deep-sea ecosystem (Mengerink et al 2014;St. John et al 2016;Martin et al 2020), to date just a few studies have used eDNA sampling to explore the deep sea (Thomsen et al 2016;Easson et al 2020;Laroche et al 2020;McClenaghan et al 2020;Govindarajan et al 2021), and none has provided insights on the deep, vertical stratification of eDNA in the ocean. Here, we observed a consistent detection of DNA of the most abundant epipelagic fish species along the water column (e.g., European anchovy is detected down to > 1000 m depth), whereas detection of DNA from deep-sea fish was restricted to the upper depth at which they were assumed to occur and below.…”
Section: Discussionmentioning
confidence: 99%
“…This material can be analyzed through metabarcoding, which allows community characterization by simultaneously sequencing a short region of the genome of multiple species, which is then compared to a reference database (Hansen et al 2018). eDNA collected from water samples can provide biodiversity information of virtually any marine habitat (Thomsen et al 2012) including deep-sea environments (Thomsen et al 2016;Laroche et al 2020;McClenaghan et al 2020). However, inferring the macroorganisms present in marine ecosystems by analyzing their DNA released into the environment requires an understanding of how DNA traces behave in the water column, and many factors related to extra-organismal DNA production rate, degradation and transport have been reported to influence its detection and concentration in the ocean (Hansen et al 2018).…”
mentioning
confidence: 99%
“…Despite the complexity of the vertical structuring of pelagic communities (Sutton 2013) and the call for studies focusing on the deep-sea ecosystem (Mengerink et al 2014;St. John et al 2016;Martin et al 2020), to date just a few studies have used eDNA sampling to explore the deep-sea (Thomsen et al 2016;Laroche et al 2020;McClenaghan et al 2020), and none has provided insights on the deep, vertical stratification of eDNA in the ocean. Here, we observed a consistent detection of DNA of the most abundant epipelagic fish species along the water column (e.g.,…”
Section: Fish Edna Stratification In the Ocean Responds To Fish Vertimentioning
confidence: 99%
“…This material can be analyzed through metabarcoding, which allows community characterization by simultaneously sequencing a short region of the genome of multiple species, which is then compared to a reference database. eDNA collected from water samples can provide biodiversity information of virtually any marine habitat (Thomsen et al 2012) including deep-sea environments (Thomsen et al 2016;Laroche et al 2020;McClenaghan et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in aquatic systems, Valentini et al (26) found that eDNA metabarcoding could more accurately detect both bony sh and amphibians compared to auditory, visual, and collection-based methods. Recently, McClenaghen et al (27) used eDNA metabarcoding to detect deep sea sh and found that the eDNA method gave similar results to conventional eld surveys while having a much lower sampling effort requirement. Additionally, eDNA metabarcoding has also been used for sediment analysis such as the study from Yoccoz et al (16) where after metabarcoding, terrestrial sediment samples were shown to correctly detect present species at the surface.…”
Section: Introductionmentioning
confidence: 99%